Factors associated with maternal near-miss at public hospitals of South-East Ethiopia: An institutional-based cross-sectional study - Ashenafi Mekonnen (SAGE Publishing, 2021)
Introduction: Maternal near-miss precedes maternal mortality, and women are still alive indicating that the numbers of near-misses occur more often than maternal mortality. This study aims to assess the prevalence of maternal near-miss and associated factors at public hospitals of Bale zone, Southeast Ethiopia. Methods: Facility-based cross-sectional study design was carried out from 1 October 2018 to 28 February 2019, among 300 women admitted to maternity wards. A structured questionnaire and checklist were used to collect data. Epi-info for data entry and statistical package for social science for analysis were used. The descriptive findings were summarized using tables and text. Adjusted odds ratio with 95% confidence interval and p-value < 0.05 were used to examine the association between the independent and dependent variables. Result: The prevalence of maternal near-miss in our study area was 28.7%. Age < 20 years, age at first marriage < 20 years, husbands with primary education, and being from rural areas are factors significantly associated with the prevalence of maternal near-miss. The zonal health department in collaboration with the education department and justice office has to mitigate early marriage by educating the community about the impacts of early marriage on health.